Mapping the trajectory of organizational leadership development: A bibliometric analysis - Talukder, Saurav Chandra; Md Miah, Tota (Acta Carolus Robertus, 2023)
This research analyzes scholarly literature on the topic of leadership development as it relates to the fields of business and management. The researchers conducted a comprehensive search of the Web of Science database covering a 15-year time frame using the PRISMA methodology, ultimately yielding 1017 documents for analysis. Biblioshiny, and VOSviewer were used for quantitative analysis and data visualization, respectively. The study provides valuable information, such as the most influential authors and their nations, the most important keywords, and the most cited scholarly works in the topic. In addition, it reveals active research areas and literature gaps that point to potential new lines of inquiry. In highlighting the managerial and structural consequences of enhancing leadership within companies, the findings provide a useful basis for policymakers and practitioners.